Assessment of 1-month conditioning program practised by equine establishment in conditioning endurance horses - Cheong, Chee Ken; Mohd Adzahan, Noraniza (2010)
Fitness indicators in horses are physiological variables such as V140, V200, VLA2 and VLA4. Endurance conditioning increases fitness level of horses. Fitness levels of 16 endurance horses from 3 different establishments practicing a similar conditioning regime were evaluated after a 1-month of conditioning. A standardized exercise test was carried out for all horses prior and after conditioning. Heart rates were monitored and blood samples were obtained throughout the exercise test and blood samples were then analyzed for lactate, cortisol, and muscle enzymes. Paired sample T-tests between pre and post conditioning were performed to evaluate the effects of 1-month conditioning program on these physiological variables. Results showed that there were no improvement in V140, V200, VLA2 and VLA4 after a 1-month conditioning program, however exercise velocity in Run 1 and AST in Run 2 were significantly different. Therefore, it was concluded that the 1-month conditioning program practiced was insufficient to increase the fitness levels of horses due to its short period and ineffective conditioning program.